2013
DOI: 10.1007/978-3-642-39799-8_21
|View full text |Cite
|
Sign up to set email alerts
|

System Level Formal Verification via Model Checking Driven Simulation

Abstract: We show how by combining Explicit Model Checking techniques and simulation it is possible to effectively carry out (bounded) System Level Formal Verification of large Hybrid Systems such as those defined using model-based tools like Simulink.We use an explicit model checker (namely, CMurphi) to generate all possible (finite horizon) simulation scenarios and then optimise the simulation of such scenarios by exploiting the ability of simulators to save and restore visited states. We show feasibility of our appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
127
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(127 citation statements)
references
References 31 publications
0
127
0
Order By: Relevance
“…In the typical case (as ours) in which model inputs are drug administrations, VPH models can be abstracted into Discrete Event Systems (DESs) (see, e.g., [23,27]), i.e., continuous-time input-state-output deterministic causal dynamical systems [38] whose input functions are discrete event sequences.…”
Section: Formalising the Virtual Physiological Human (Vph) Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In the typical case (as ours) in which model inputs are drug administrations, VPH models can be abstracted into Discrete Event Systems (DESs) (see, e.g., [23,27]), i.e., continuous-time input-state-output deterministic causal dynamical systems [38] whose input functions are discrete event sequences.…”
Section: Formalising the Virtual Physiological Human (Vph) Modelmentioning
confidence: 99%
“…Invariants and goals for the treatment being sought can be modelled as continuous-time monitors embedded within the VPH (DES) model, along the lines of [23,28]. Monitors observe the state of the system and check whether the properties of interest are satisfied.…”
Section: Modelling Treatment Invariants and Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in this direction was carried out by Amla et al [10] who have describes eight bounded and unbounded techniques, and analyzes the performance of these algorithms on a large and diverse set of hardware benchmarks. Most recently, Mancini et al [11] showed how by combining Explicit Model Checking techniques and simulation it is possible to carry effectively out (bounded) System Level Formal Verification of large Hybrid Systems such as those defined using model-based tools like Simulink. The authors use an explicit model checker (namely, CMurphi) to generate all possible (finite horizon) simulation scenarios and then optimize the simulation of such scenarios by exploiting the ability of simulators to save and restore visited states.…”
Section: Related Work Of Model Checkingmentioning
confidence: 99%
“…Thus the verification is automated and complete. Moreover, the approach of system level formal verification to exploit a simulator in order to carry out formal verification has been further developed in [32,33] and applied to biological contexts. Finally, all these approaches use the explicit model checker CMurphi [34].…”
Section: Related Workmentioning
confidence: 99%